Survey of Neisseria gonorrhoeae antimicrobial susceptibility in Ontario - Loo, Vivian G (Pulsus Group Inc, 1990)
The minimal inhibitory concentrations (MICs) of penicillin, tetracycline, erythromycin, cefoxitin, ceftriaxone and spectinomycin were determined for 300 consecutive strains of Neisseria gonorrhoeae collected from physicians’ offices in Ontario. Only four isolates were found to produce beta-lactamase. Of the remaining 296 isolates, five (1.7%) had penicillin MICs greater than or equal to 1 mg/L, 78 (26.3%) had tetracycline MICs greater than or equal to 1 mg/L, 13 (4.4%) had cefoxitin MICs greater than or equal to 1 mg/L and 43 (14.5%) had erythromycin MICs greater than or equal to 1 mg/L. Two isolates (0.7%) had high level tetracycline resistance with MICs greater than or equal to 16 mg/L. All N gonorrhoeae isolates were susceptible to ceftriaxone and to spectinomycin.